Scholarium Dan Arena Produksi Pengetahuan - Tomi Setiawan (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2018)
This paper is the result of a literature review that discusses the activity of scholarium and arena of knowledge production in university, specifically in the Majors of Rural Sociology, Bogor Agricultural University. The university in general is an institution with the highest respectability in the academic environment. Then the university became the instrument of social climbing for most people in developing country society. The objective difference in the science of Rural Sociology with other universities is in the context of 'agriculture'. More specifically Sajogyo then give eco-sociology term. Eco-sociology is applied sociology in the sociological sense that applied to human natural ecosystems. Furthermore, the reorientation of curriculum development should be presented as a collective development process and laid in the unity of theory and practice, and conceived as a constant dialogue among different scholars from different disciplines. In the end the benefit of science for the public is not denied, but the community needs should not be dictated to science as if intellectuals are no longer free to seek scientific truth as an end in itself, but the purpose of which is determined by the needs of the community.